Free gingival grafting of single tooth recession with advanced-platelet-rich fibrin as a palatal bandage: A 12-month follow-up - Avita Rath; Melissa Wong Li Zheng; Bennete Fernandes; H R Priyadarshini (Wolters Kluwer Medknow Publications, 2022)
Although techniques such as subepithelial connective tissue graft are now widely used for root coverage procedures, free gingival graft (FGG) continues to be a common mucogingival procedure used to increase keratinized tissue dimensions. However, the palatal donor site heals with secondary intention and requires a longer healing time causing more discomfort and pain to the patient. A healthy 22-year-old female patient presented with Miller's class II recession in relation to the tooth 31 with high frenal attachment and a shallow vestibule, which was treated using FGG, and the donor site was bandaged with advanced-platelet-rich fibrin (A-PRF). This report evaluates the healing of the donor site over a 12-month period and assesses the root coverage as well as the postoperative discomfort after the harvesting of graft. In terms of healing, the use of A-PRF membrane as a palatal bandage appears to accelerate healing at the donor site, thereby reducing postoperative complications.